2019
DOI: 10.1103/physrevlett.122.153903
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Wave Propagation in Multimode Systems with Correlated Noise

Abstract: Imperfections in multimode systems lead to mode-mixing and interferences between propagating modes. Such disorder is typically characterized by a finite correlation time (in quantum evolution) or correlation length (in paraxial evolution). We show that the long-scale dynamics of an initial excitation that spread in mode space can be tailored by the coherent dynamics on short-scale. In particular we unveil a universal crossover from exponential to power-law ballistic-like decay of the initial mode. Our results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…( 1) is particularly useful when the nonlinearity is weak. Equations ( 1) and ( 2) also describe multimode optical fibers 25,43,44 or multimode resonators [45][46][47] , Figs. 1d,e respectively.…”
Section: General Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…( 1) is particularly useful when the nonlinearity is weak. Equations ( 1) and ( 2) also describe multimode optical fibers 25,43,44 or multimode resonators [45][46][47] , Figs. 1d,e respectively.…”
Section: General Formalismmentioning
confidence: 99%
“…A decisive step along these lines has been achieved recently by the authors of Ref. 19,26 which, assuming thermal equilibrium conditions and weak non-linearity, have established a comprehensive 41,42 ; (c) A multicore fiber 25 ; (d) A multimode fiber 25,43,44 ; (e) Deformed multimode (micro-) resonator with underlying chaotic dynamics [45][46][47] ; (f) A network of coupled "soft" (size-modulated) spins. The corresponding Hamiltonian has similarities but also crucial differences with the Hamiltonian that describes a photonic multimode network.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction 7 tion length between segments, the mean propagation constant spacing, and the strength of the perturbation that mixes the modes. These two chapters are based on a research paper that was recently published in Physical Review Letters [13].…”
Section: Outline Of the Thesismentioning
confidence: 99%
“…In our publication [13], we reported that the scale of environmental disorder correlation length plays an important role in dictating the transition between different dynamics regimes. We set two thresholds of z c , separating three regimes:…”
Section: Random Matrix Modelmentioning
confidence: 99%
See 1 more Smart Citation